Pembelajaran Karya Ilmiah Menggunakan Media Powtoon untuk Siswa SMA Kolese De Britto Kelas XI Bahasa - Rishe Purnama Dewi; Agustinus Prih Adiartanto (Jurusan Tadris Bahasa Indonesia, 2021)
This study aims to develop learning media for writing scientific papers material using the Powtoon for students of SMA Kolese De Britto class XI Bahasa. The focus of this research is to produce Powtoon media that developed in five stages. The five-stage were (1) the study of lesson plans and teaching materials; (2) the study of materials and sources of teaching materials; (3) media development; (4) expert validation; and (5) final product review. Product validation was validated by two experts, namely language learning experts and media experts. The Product was trialled on eighteen students of SMA Kolese De Britto class XI Bahasa. The results of product validation were obtained through quantitative descriptive calculations using a five-scale conversion basis. The validation of the media products according to the product language learning expert is 4.44, the result of the media validation expert is 4.50, and the validation result by the students is 4.60. Based on the validation results, the media produced is classified as very good and can be used in learning.Penelitian ini bertujuan mengembangkan media pembelajaran menulis karya ilmiah bermedia Powtoon untuk siswa SMA Kolese De Britto kelas XI Bahasa. Fokus penelitian ini menghasilkan media Powtoon dengan materi karya ilmiah yang dikembangkan melalui lima tahapan, yaitu (1) tahap pengkajian RPP dan materi ajar, (2) tahap pengkajian bahan dan sumber bahan ajar, (3) pengembangan media, (4) validasi ahli, dan (5) kajian produk akhir. Validasi produk dilakukan oleh dua ahli, yaitu ahli pembelajaran bahasa dan ahli media. Uji coba produk dilaksanakan pada delapan belas siswa SMA Kolese De Britto kelas XI Bahasa. Hasil validasi produk diperoleh melalui perhitungan deskriptif kuantitatif yang menggunakan dasar konversi skala lima. Hasil validasi produk media menurut ahli pembelajaran bahasa produk sebesar 4,44, hasil validasi ahli media sebesar 4,50, dan hasil validasi uji coba subjek pengguna sebesar 4,60. Media pembelajaran yang dihasilkan tergolong sangat baik dan dapat dipergunakan dalam pembelajaran.